Immediate adverse events following COVID-19 immunization. A cross-sectional study of 314,664 Italian subjects.: Immediate adverse events following COVID-19 immunization - Gianfredi, Vincenza; Minerva, Massimo; Casu, Giulia; Capraro, Michele; Chiecca, Greta; Gaetti, Giovanni; Mantecca Mazzocchi, Rosaria; Musarò, Patrizia; Berardinelli, Pasquale; Basteri, Paola; Bertini, Beatrice; Ferri, Camilla; et al. (Acta Biomedica Atenei Parmensis, 2021)
Background and aim: The urgency of having rapidly safe and efficient COVID-19 vaccines called for the need to shorten trial phases, reduce sample sizes, and speed-up the approval process by the regulatory Agencies. In light of this, monitoring adverse effects (AEFI) (both immediate and at medium-long term) become of great importance. Aim of this cross-sectional study was to explore the associations between several factors and risk of immediate AEFI. Methods: Data come from the electronic dataset developed ad hoc to record demographic data, anamnesis and data related to immunization, set-up in the mass vaccination site in Novegro (Milan). Novegro mass vaccination site was one of the mass vaccinations sites with the highest flow in Lombardy Region, with a maximum capacity of 5,000 vaccinations/day. The center opened in April 2021 and closed the 1st of August 2021. A multivariable logistic regression model was used. Odds ratios adjusted (aOR) for age and sex are presented. Statistical significance was set at p<0.05. Analyses were conducting using STATA. Results: Among the total of 314,671 subjects vaccinated, 0.5% developed an immediate AEFI, on average 17.0 ± 0.43 minutes after the administration. The three most frequent AEFI recorded were vagal response (30%), anxiety reaction (24%) and dizziness (21%). AEFI were more frequently observed among women [aOR= 2.24 (95%CI= 2.00 - 2.50)], and those with at least one previous disease [aOR= 1.47 (95%CI= 1.22-1.76)]. Conclusions: In conclusion, AEFI were less likely to occur for increasing age and after the second dose. Results from this large, complete and representative sample population regarding enrich the interesting scientific debate on potential adverse events following COVID-19 immunization.